F-wave studies in diabetes mellitus: A comparison between pre-symptomatic and symptomatic patients with distal sensory polyneuropathy - de Souza, Rainha J.; de Souza, Aaron; Nagvekar, Meera D. (Neurology, psychiatry, and brain research, 2018)
•We present F-wave parameters in diabetic patients with and without symptoms of distal sensory polyneuropathy (DSPN).•153 patients recruited: 51 controls, 50 asymptomatic diabetics, and 52 diabetics with symptoms of DSPN.•All had blood glucose and glycosylated haemoglobin estimation and nerve conduction studies including F-wave studies.•Diabetic patients show prolonged F-mean latencies and early reduction in F-persistence, with further change in F-latencies after symptoms appear.•Neuropathic pain and abnormal neurological examination correlated with changes in F-parameters. We present F-wave parameters in diabetic patients with and without symptoms of distal sensory polyneuropathy (DSPN), and correlate altered F-parameters in diabetic patients with glycaemic control and clinical features of DSPN. Over one year, diabetic patients with and without symptoms of DSPN, as well as controls were recruited. After detailed history and examination, 153 patients (51 controls, 50 pre-symptomatic diabetics, and 52 symptomatic diabetics) had standard nerve conduction studies including F-wave studies on the right median, ulnar and common peroneal nerves, along with blood glucose and glycosylated haemoglobin estimation. Symptomatic diabetics had poorer glycemic control and longer duration of diabetes. Non-diabetic and diabetic subjects showed differences in F-wave persistence and minimum, maximum, and mean latencies. F-wave persistence and mean latency differed between non-diabetic patients and pre-symptomatic diabetics. Symptomatic diabetics showed further prolongation of minimum, maximum and mean F-latencies. Overall, F-minimum and mean latencies were consistently affected in diabetic patients, while chronodispersion showed no change. Neuropathic pain, but not other symptoms, correlated significantly with changes in F-wave latencies. An abnormal motor or sensory examination correlated with prolonged F-latencies and reduced F-persistence. Abnormal F-parameters correlated with diabetes duration and glycosylated haemoglobin levels. Diabetic patients show a high incidence of subclinical F-wave abnormalities including prolonged F-mean latency and early reduction in F-persistence, with further prolongation in F-mean, minimum and maximum latencies after symptoms appear without significant changes in persistence or chronodispersion. F-wave parameters were significantly correlated with positive sensory symptoms, abnormalities on neurological examination, diabetes duration and glycaemic control.